Extracellular Vesicles Released from Neprilysin Gene-Modified Human Umbilical Cord-Derived Mesenchymal Stem Cell Enhance Therapeutic Effects in an Alzheimer's Disease Animal Model. (3rd December 2021) - Jeong, HyeJu; Kim, Ok Joon; Oh, Seung-Hun; Lee, Sanghoon; Reum Lee, Han A.; Lee, Kee Ook; Lee, Boo-Yong; Kim, Nam Keun
Abstract : Alzheimer's disease (AD) animal studies have reported that mesenchymal stem cells (MSCs) have therapeutic effects; however, clinical trial results are controversial. Neprilysin (NEP) is the main cleavage enzyme of β -amyloid (A β ), which plays a major role in the pathology and etiology of AD. We evaluated whether transplantation of MSCs with NEP gene modification enhances the therapeutic effects in an AD animal model and then investigated these pathomechanisms. We manufactured NEP gene-enhanced human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) and intravenously transplanted them in A β 1-42 -injected AD animal models. We compared the differences in behavioral tests and immunohistochemical assays between four groups: normal, A β 1-42 injection, naïve hUC-MSCs, and NEP-enhanced hUC-MSCs. Both naïve and NEP-enhanced hUC-MSC groups showed significant improvements in memory compared to the A β 1-42 injection group. There was no significant difference between naïve and NEP-enhanced hUC-MSC groups. There was a significant decrease in Congo red, BACE-1, GFAP, and Iba-1 and a significant increase in BDNF, NeuN, and NEP in both hUC-MSC groups compared to the A β 1-42 injection group. Among them, BDNF, NeuN, GFAP, Iba-1, and NEP showed more significant changes in the NEP-enhanced hUC-MSC group than in the naïve group. After stem cell injection, stem cells were not found. Extracellular vesicles (EVs) were equally observed in the hippocampus in the naïve and NEP-enhanced hUC-MSC groups. However, the EVs of NEP-enhanced hUC-MSCs contained higher amounts of NEP as compared to the EVs of naïve hUC-MSCs. Thus, hUC-MSCs affect AD animal models through stem cell-released EVs. Although there was no significant difference in cognitive function between the hUC-MSC groups, NEP-enhanced hUC-MSCs had superior neurogenesis and anti-inflammation properties compared to naïve hUC-MSCs due to increased NEP in the hippocampus by enriched NEP-possessing EVs. NEP gene-modified MSCs that release an increased amount of NEP within EVs may be a promising therapeutic option in AD treatment.